Building and estimating total cost of web based Fraud Detection System in Microsoft Azure Cloud Platform - Gagandeep Kaur, Dr Harsh Kumar (International Journal of Advanced Science and Technology, 2020)
The cloud computing as a booming technology provides a scaled computing resources fromindividual users to larger sized organizations at economical cost. However there are lot of chances toget increased costs in cloud computation due to unclear knowledge on cloud computing resources incloud platforms and unrealistic cost estimations. Every business requires unique kind of cloud modeland specific resources requirements for its business setup. Analysing and finding best cloud modelwas considered a harder task while working on real cloud platforms. This paper addresses thedifficulties in selecting appropriate cloud resources that needs to be matched to businessrequirements. We build a web based fraud detection system and estimating its costs in MicrosoftAzure cloud platform. The proposed fraud detection system utilizes the Microsoft Azure’ cloudresources for performing operations like analytics and storage..